Analysis of Motivation and Work Discipline in Improving Kindergarten Teacher Performance: A Case Study in Kutablang District - Bariah, Chairul; Yana, Sri; Imanda, Riska (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Teacher performance in the science teaching and learning process is an important indicator of achieving educational goals. This is the background to this research related to the low performance of teachers in kindergartens/early childhood education in Kutublang District. This study aims to analyze the influence of work discipline (X1) on teacher performance (Y); work motivation (X2) on teacher performance (Y), and the influence of both together on the performance of kindergarten/early childhood education teachers in Kutublang District. This study is a quantitative correlational study with a sample of 120 teachers. Sampling used a random technique, with all correlation tests using the SPSS program. The results of the study illustrate that there is a significant correlation between work discipline (X1) and teacher performance (Y) of 56.6% with the weakest dimension being adherence to time rules, the correlation between work motivation (X2) and teacher performance (Y) of 8.9% with weaknesses in the intrinsic motivation dimension, and a significant correlation between the two variables X1 and X2 simultaneously on teacher performance (Y) in TK/PAUD in Kutablang District of 56.2% with the regression equation Ŷ = 18.787 + 2.083 X1 + 0.154 X2. Based on the results of the study, the researcher provides recommendations that teachers should improve discipline, motivation, and achievement in carrying out work with a full sense of responsibility, and school leaders should always monitor teacher performance in science learning and provide encouragement so that teachers are motivated to improve work discipline.